THE EFFECT OF ATTITUDE, SUBJECTIVE NORMS, AND TRUST ON BUSINESS GROWTH IN SME IN TANGERANG SELATAN - Hidayah, Nur; Rodhiah, Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
According to the Organization for Economic Cooperation and Development (OECD), small and medium enterprises (SMEs) account for more than 95% of generating huge new jobs. There are many factors that need to be considered so that SMEs can continue to run well. One of the factors that need to be considered by entrepreneurs is the growth and development of the business they will undertake. The purpose of this study was to investigate the effect of attitudes, subjective norms and self-confidence of entrepreneurs on the growth of business results. The sample to be taken for this research is SMEs located in South Tangerang. By convenience sampling, as many as 90 SMEs. The technique of collecting data is by distributing questionnaires to the owners of SMEs who are the research sample. In testing empirically the research model uses a partial least squares (PLS) path modeling approach. The results of the study show subjective beliefs and norms have no effect on the growth of operating results. Attitude has an influence on the growth of business results. Keywords: Attitude, Subjective Norm, Self-Confidence, Growth